Experimental investigation on thermal performance of natural draft wet cooling towers employing an innovative wind-creator setup. (15th August 2016) - Alavi, Seyed Rashid; Rahmati, Mehdi
Graphical abstract: Highlights: An innovative wind-creator setup is provided to implement intrinsic features of the wind. A twofold trend is exhibited by outputs with respect to the cross-wind variation. Influences of cross-wind velocity, inlet water temperature and water flow rate are studied. Regression analysis is utilized so as to develop general mathematical equations. A guideline is recommended for the purpose of reaching optimum operating conditions. Abstract: Natural draft wet cooling towers are one of the most widely-used types of wet cooling towers in the large-scale power plants. In the present research, the heat transfer performance of natural draft counter-flow wet cooling towers is investigated under cross-wind and windless conditions by virtue of an innovative wind-creator setup provided so as to implement intrinsic features of the natural wind speed profile precisely. As a matter of fact, this investigation will focus on the influences of cross-wind velocity, inlet water temperature and water flow rate on the water temperature difference and cooling efficiency of the studied cooling tower, with an emphasis on the role of wind speed features. Interestingly, a twofold trend is exhibited by the water temperature difference and cooling efficiency with respect to variation of the cross-wind velocity. Furthermore, to have a more applicable study, regression analysis of the experimental results is utilized for the sake of developing general mathematical equations and thus facilitating further analyses. Finally, these mathematical equations are employed in order to recommend a guideline for the purpose of reaching optimum operating conditions of natural draft wet cooling towers.